PENGARUH MINAT MEMBACA KARYA SASTRA DAN KREATIVITAS TERHADAP KETERAMPILAN MENULIS NOVEL - Endang Sri Sulasih (Universitas Nasional, 2016)
ABSTRACTThis study aims to determine the effect of interest in reading literature and creativity both in themselves individuallyor collectively - against novel essay writing skills, students in class XI of Private Vocational HighSchool Pondok Bambu in East Jakarta. The research uses survey method. Samples were taken from 82 studentsgrade XI, Pusaka 1 Vocational High School in East Jakarta.Data was collected by questionnaire and an essaywriting test novel. Data analysis using linear regression method. The results of the study is:1Keywords: Interest in reading literature, creativity, novel writing skills